Mass rabies exposure of veterinary health care workers in Germany: Management, immune response, and tolerability of post exposure-prophylaxis - Lennart Lemmermann; Jonathan Remppis; Sabine Bélard; Florian Steiner (One Health)
Background: Rabies is a fatal zoonotic disease caused by Rabies lyssavirus, primarily transmitted through dog bites. In 2008, Germany was declared free from terrestrial rabies by the WOAH. However, illegal pet imports can still lead to rabies exposure, as seen in the 2021 case of a rabid puppy illegally imported to Germany, resulting in a mass exposure incident. Methods: This retrospective study assessed the post-exposure management of 39 veterinary clinic staff exposed to the rabid puppy, focusing on the practicability, immunogenicity, and tolerability of post-exposure prophylaxis (PEP). Data was collected from patient records and for follow-up by phone using standardized case record forms, entered into an Excel database, and analyzed descriptively. Ethics approval was obtained from the Ethics Committee of the University of Tübingen (8452022BO2). Results: Exposed individuals received varying PEP regimens based on vaccination status and exposure level, including possible aerosol exposure. Most followed the Essen-Scheme, with some receiving human rabies immune globulin (hRIG). All developed protective antibody titers, and adverse reactions were generally mild. Conclusion: This case highlights challenges in rabies mass exposure management and emphasizes needs for continued preparedness, resource allocation and education about rabies, even in regions considered rabies-free.